PENGGUNAAN PELEMBAP PADA BAYI BERISIKO TINGGI TERHADAP INSIDENS DERMATITIS ATOPIK INFANTIL: SEBUAH TELAAH SISTEMATIK (Media Dermato Venereologica Indonesiana, 2020)
Introduction: Atopic dermatitis is a relapsing chronic inflammatory skin disease, 15-20% occurring in children. Heredity in the family is the most crucial risk factor for the incidence of atopic dermatitis. Therefore, improving the barrier function of the skin as early as possible in high-risk infants may be an option as primary prevention for atopic dermatitis. Objective: Conducting a systematic review of randomized controlled trials (RCT) that test the effects of giving moisturizers to high-risk infants and the incidence of infantile atopic dermatitis. Methods: A literature search was carried out through three electronic databases: PubMed, Cochrane, and Embase. Those articles were critically reviewed and assessed for the risk of bias using the Cochrane Risk of Bias Tools. Results: After a critical review of the full text, there were 4 RCT articles. Those four articles found a similar outcome: the incidence of atopic dermatitis was lower in the intervention group. Discussion: The link between heredity and the incidence of atopic dermatitis in children forms the basis of inclusion criteria for samples in this systematic review. Moisturizer administration has been shown to improve TEWL values and stratum corneum hydration. Conclusion: The use of moisturizers in high-risk infants may be considered as one of the preventive interventions for atopic dermatitis. However, further research is needed to support this hypothesis.